The effects of acute tryptophan depletion on speech and behavioural mimicry in individuals at familial risk for depression. (March 2016) - Hogenelst, Koen; Sarampalis, Anastasios; Leander, N Pontus; Müller, Barbara CN; Schoevers, Robert A; aan het Rot, Marije
Major depressive disorder (MDD) has been associated with abnormalities in speech and behavioural mimicry. These abnormalities may contribute to the impairments in interpersonal functioning that are often seen in MDD patients. MDD has also been associated with disturbances in the brain serotonin system, but the extent to which serotonin regulates speech and behavioural mimicry remains unclear. In a randomized, double-blind, crossover study, we induced acute tryptophan depletion (ATD) in individuals with or without a family history of MDD. Five hours afterwards, participants engaged in two behavioural-mimicry experiments in which speech and behaviour were recorded. ATD reduced the time participants waited before speaking, which might indicate increased impulsivity. However, ATD did not significantly alter speech otherwise, nor did it affect mimicry. This suggests that a brief lowering of brain serotonin has limited effects on verbal and non-verbal social behaviour. The null findings may be due to low test sensitivity, but they otherwise suggest that low serotonin has little effect on social interaction quality in never-depressed individuals. It remains possible that recovered MDD patients are more strongly affected.